Building values: a collaborative, participatory and empowerment evaluation of civics and religion curricula in three Tanzanian schools - Sulayman, Hamdun Ibrahim (My University, 2009)
ABSTRACT In this study the question of how to address corruption in Tanzanian society is considered from the view point of learning positive values to contribute to reducing corruption now and in the future. It is argued that by strengthening the teaching of positive values to provide a foundation in values as alternatives for students to consider, may impact their decisions while still at school and later in life as adults and leaders for them to resist corruption when encountered. The study arises from Transparency International surveys consistently ranking Tanzania early in the new millennium amongst the 10 most corrupt countries internationally. Given the failure of national commissions in Tanzania, legal institutions such as the Prevention of Corruption Bureau, initiatives emanating from the office of the Presidency, amongst others, to stem corruption, here it is argued for the use of education as state institution to strengthen values teaching in 3 programmes in the state curriculum through evaluation to address the problem. Adopting an approach to evaluation which draws teachers into the process for them to drive it in part, developed by Fetterman and Wandersman, capacity can be built within schools to do so, an approach which is somewhat different to the norm where this capacity more frequently may be driven from outside, coercive, and be disempowering of agents of change within schools. Using the stepped procedure as well as the ‘facets’ of this participatory approach to evaluating the 3 positive values curricula, and with coaching by the evaluator, a measure of self-determination seemed experienced by teachers to teach values like honesty and self-respect, self-reliance and personal integrity, amongst others, to assist students resist corrupt practices when encountered. Multiple self-administered instruments developed with teachers helped gauge teachers progress towards goals they set themselves to achieve in one academic year and assisted to build confidence in addressing this issues through schooling, the sample of schools in the study being purposefully selected as they educate between them more than half the professional and political leaders in the nation. The study aimed to find what positive values are taught in 3 curricula [Civics, Islamic Knowledge, Bible Knowledge], and how these are taught, as well as to find out if this teaching was strengthened through using the tools of empowerment evaluation. The data indicates firstly, shared values across these curricula and values specific to each are taught, to provide alternatives for learners to consider prior to action. This foundational guide for students seemed strengthened if secular values are allied to religious values to provide value-informed choices for students, and that this foundation may be further strengthened with self-directed changes to the curriculum being made by teachers. Secondly, traditional pedagogical methods seem to be less effective where values teaching is not linked to exemplarily teacher behaviour, parables and storytelling, and moral actions of role models emulating how to act morally. Thirdly, teaching positive values was found to be strengthened through self-evaluation, as teachers seemed to experience a measure of empowerment or self-determination in the evaluation, and to aim at self-improving effective teaching of values. Finally, data indicates that where teachers are drawn into the evaluation process, trained in these techniques facilitated by an evaluator, that refinements to values teaching may be sustained in the short to medium term, following the withdrawal of the evaluator from the field. Findings were corroborated in part through triangulating the data, here with data from naturalistic observations and questionnaires particularly. Amongst recommendations made in the light of the study, one is the importance of the state employing religious teachers, as opposed to these being functionaries of the mosque and church as at present, a second being that positive values be made part of the compulsory core curriculum in all schools in the system.
Keywords: Positive values; Civics; Islamic Knowledge (IK); Bible Knowledge (BK); Curriculum; Collaborative participatory and empowerment evaluation; Evaluator; Coach; Corruption; Takrima; Moral choices; Decision